public spaces - Grigoryeva, Elena (project baikal, 2013)
The topic of this issue is PUBLIC SPACES. It is familiar and clear to every citizen. The streets and courtyards as childhood experiences remain with us forever. And these are the places where we come with our parents at weekends, where we meet friends, where we have dates and where we already come for a walk with our children. The history of public spaces is long and captivating. It was the main city squares where the most important events took place in history. The Agoras of Ancient Greece and the Roman Forums, the squares of Vatican, Paris and London, Moscow and Saint Petersburg… Greve, Trafalgar, Senate, Palace, Red, Bolotnaya – behind every name there is life of capitals, countries and nations. Public spaces, their shapes, image and development greatly influence the perception of the city as a whole. Both visitors and inhabitants can see in public spaces not only the visage but the heart, the soul and the mind of the city. Unfortunately, sometimes we have to prove the value of public spaces and defend them from those who consider them nothing but a blank space, nobody’s land destined for barbarous development. What should happen to make citizens perceive public spaces as their own and to make authorities consider development and maintenance of squares and parks their priority task against the background of increasing competition between cities and the fight for human capital? Lately they more often say about “a high-quality human capital”. And now, when they say “the city should be liveable” they add “for all groups of citizens, including the creative class”.